Observations of 14CO2 in ecosystem respiration from a temperate deciduous forest in Northern Wisconsin. Issue 4 (14th April 2015) - Phillips, Claire L.; McFarlane, Karis J.; LaFranchi, Brian; Desai, Ankur R.; Miller, John B.; Lehman, Scott J.
Abstract The 14CO2 composition of plant and soil respiration can be used to determine the residence time of photosynthetically fixed carbon before it is released back to the atmosphere. To estimate the residence time of actively cycled carbon in a temperate forest, we employed two approaches for estimating the Δ14CO2 of ecosystem respiration (Δ14C‐Reco) at the Willow Creek AmeriFlux site in Northern Wisconsin, USA. Our first approach was to construct nighttime Keeling plots from subcanopy profiles of Δ14CO2 and CO2, providing estimates of Δ14C‐Reco of 121.7‰ in June and 42.0‰ in August 2012. These measurements are likely dominated by soil fluxes due to proximity to the ground level. Our second approach utilized samples taken over 20 months within the forest canopy and from 396 m above ground level at the nearby LEF NOAA tall tower site (Park Falls, WI). In this canopy‐minus‐background approach we employed a mixing model described by Miller and Tans (2003) for estimating isotopic sources by subtracting time‐varying background conditions. For the period from May 2011 to December 2012 the estimated Δ14C‐Reco using the Miller‐Tans model was 76.8‰. Together, these Δ14C‐Reco values represent mean Reco carbon ages of approximately 1–19 years. We also found that heterotrophic soil‐respired Δ 14C at Willow Creek was 5–38‰ higher (i.e., 1–10 years older) than predicted by the Carnegie‐Ames‐Stanford Approach global biosphere carbon model for the 1 × 1 pixel nearest to the site. This study provides much needed observational constraints of ecosystem carbon residence times, which are a major source of uncertainty in terrestrial carbon cycle models.